2005
DOI: 10.5057/kei.5.3_51
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aroma on Event-Related Potential in Cognitive Workload

Abstract: We investigated the effect of aroma on the event related potential (ERP) during certain cognitive workload. In this study we regard repeated oddballtask as our cognitive woridoad, while the oddball task itself is used to be considered as the cognitive task for investigating the event related potential under the auditory stimuli. We used the oddball task consisting of three kinds of tones. The oddball task used in this study was consisted of three kinds of auditory stimuli. The auditory oddball operation task w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The findings indicated that intermittent odorant presentation enhance relaxation state and thus, reduce cognitive loadings due to Stroop interference that was counting pieces of digits. Previous studies showed cognitive loading was reduced by pleasant odor during word-color Stroop task [3] and oddball task [4]. Former study showed O 2 Hb in left forehead was significantly increased when pleasant odors, lavender and peppermint, were presented.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The findings indicated that intermittent odorant presentation enhance relaxation state and thus, reduce cognitive loadings due to Stroop interference that was counting pieces of digits. Previous studies showed cognitive loading was reduced by pleasant odor during word-color Stroop task [3] and oddball task [4]. Former study showed O 2 Hb in left forehead was significantly increased when pleasant odors, lavender and peppermint, were presented.…”
Section: Discussionmentioning
confidence: 96%
“…Some studies report that, during aromatherapy, patients stir a memory from the past [8,9]. The other studies tested cognitive function of healthy subject reported that aroma presentation enhances cognitive function during cognitive task [3,4]. The studies suggest aroma sensation relieve symptoms of dementia patients.…”
Section: Introductionmentioning
confidence: 91%
“…Inhaling essential oils reduces stress (Chamine & Oken, 2016 ; Heuberger et al., 2006 ; Höferl et al., 2016 ; Kim et al., 2011 ; Motomura et al., 2001 ; Shimada et al., 2011 ; Toda & Morimoto, 2008 ), maintains concentration (Ho & Spence, 2005 ; Kaneki et al., 2005 ), and improves sleep (Fismer & Pilkington, 2012 ; Hirokawa et al., 2012 ) and dementia symptoms (Ballard et al., 2002 ; Holt et al., 2003 ; Smallwood et al., 2001 ) in humans. Human cognitive functions, including perception, attention, memory, language, thought, and emotion, collectively facilitate higher‐order processing, including decision making and creativity.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that aroma stimulating olfactory perception not only reduce psychological stress [6] but also makes people sensed odorant to evoke variant psychological impression [16]. People can determine the food freshness and food qualities, as whether the food is edible or not, from odor thrown out from foods.…”
Section: Introductionmentioning
confidence: 99%